The end of Ottoman rule in Bosnia - Grandits, Hannes, author.
1 online resource.
Keywords: "This book focuses on the end of four centuries of Ottoman rule in Bosnia and Herzegovina in the 1870s. After an introduction to the region and the political zeitgeist of the late 1860s and early 1870s, it examines in detail the dramatic years beginning in the summer of 1875, when the outbreak of violent unrest in the eastern Herzegovinian region bordering Montenegro led to a massive refugee catastrophe. The study traces the surprising further political and social dynamics to the summer and fall of 1878, when a Habsburg army finally invaded the Bosnian Vilayet and took control of the province - but only after months of fighting against massive local resistance throughout the province. This book cannot be viewed in isolation from larger political dynamics, which are also constantly present in this study as they unfolded. However, as this book attempts to show, it is hardly possible to understand the often contradictory effects of these larger political dynamics without delving deeper into the complex local rationalities and constraints on the action of the actors involved in them. The End of Ottoman Rule in Bosnia will appeal to students, teachers, and researchers in late Ottoman and Bosnian history"--